Allergic sensitization increases contractile responses to 5-HT in guinea pig aorta - Campos-Bedolla, P; De-La-Cruz-Negrete, R; Vargas, M H; Torrejón-González, E; Mejía-Mendoza, D; Islas-Hernández, A; Segura-Medina, P; Córdoba-Rodríguez, G; Orozco-Suárez, S; Arreola-Ramírez, J L (Physiological research, 2020)
Epidemiological and clinical studies suggest that asthma is associated with adverse cardiovascular outcomes, but its mechanism is uncertain. 5-Hydroxytryptamine (5-HT) is a mediator involved in asthma and in cardiovascular functioning. Thus, in the present study, we explored whether allergic sensitization in guinea pigs modifies 5-HT-induced contractile responses and 5-HT2A receptor expression in thoracic aorta rings. We found that sensitization produced a significant increase of 100 microM 5-HT-induced contractions of aorta rings (~27 % greater contraction than in non-sensitized animals, p<0.05). Preincubation with 10 nM ketanserin (a 5-HT2A receptor antagonist) reduced by ~30 % (p=0.003) and ~36 % (p=0.005) the area under the curve of 5-HT-induced contractions in aortas from non-sensitized and sensitized animals, respectively. There were no differences between sensitized and non-sensitized animals with respect to mRNA (qPCR) and protein (Western blot) expression of 5-HT2A receptor in thoracic aortas. We concluded that in this guinea pig model of asthma, allergic sensitization is not confined to airways, but also affects arterial contractile responses to 5-HT; changes in the expression of the 5-HT2A receptor appear not to be involved in this phenomenon.
Keywords: morčata; Animals; Serotonin; Muscle, Smooth, Vascular; Guinea Pigs; receptor serotoninový 5-HT2A; aorta; serotonin; Aorta; zvířata; mužské pohlaví; Male; modely nemocí na zvířatech; Receptor, Serotonin, 5-HT2A; bronchiální astma; svaly hladké cévní; Asthma; Disease Models, Animal